PAI TEACHER PEDAGOGIC COMPETENCE IN IMPROVING STUDENTS' INTEREST AND ACHIEVEMENT IN ELEMENTARY SCHOOLS IN BANDUNG CITY - Hanafiah Hanafiah; Sutarman Sutarman (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The research objective to be achieved is the pedagogical competence of PAI teachers in increasing the interest and learning achievement of students at SDN Cicadas 2 Bandung City. A qualitative method, data sources in the study consisted of the school principal, deputy head of curriculum, and three Fiqh teachers and profile documentation of SDN 2 Kota Bandung. Collecting data in this research uses interview observations at research locations in schools observing phenomena that occurred and documentation studies in the form of photos of teacher learning activities, official meeting notes, archives related to teacher competence pedagogy, books that support the focus of research to complement the above data. The results of the discussion above can be drawn several conclusions, namely as follows: (1). The Pedagogic Competence of PAI Teachers at SDN 2 Cicadas Bandung City has been well implemented, consisting of six components including student understanding, learning design, educational and dialogic learning, learning technology, evaluation of learning outcomes, student development; (2). Student interest in PAI subjects at SDN Cicadas 2 Bandung City. with indicators of feeling happy about PAI subjects, student interest in learning, attention shown during learning, and student involvement by responding in each lesson both asking and giving responses submitted by PAI teachers; (3). The learning achievement of students at SDN Cicadas 2 Bandung City in the academic field includes knowledge, and the results of report cards have increased.